2021
DOI: 10.1002/jso.26564
|View full text |Cite
|
Sign up to set email alerts
|

Towards standardization of management of gallbladder carcinoma with obstructive jaundice: Analysis of 113 cases over 10 years at a single institution

Abstract: Background Presence of jaundice in gallbladder carcinoma (GBC) is considered a sign of inoperability with no defined treatment pathways. Methods Retrospective analysis of all surgically treated GBC patients from January 2010 to December 2019 was performed for evaluating etiology of obstructive jaundice, resectability, postoperative morbidity, mortality, disease‐free survival (DFS) and overall survival (OS). Results Out of 954 patients, 521 patients (54.61%) were locally advanced gallbladder carcinoma (LAGBC: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The recurrence rate of GBC jaundice patients is usually high, as seen in the study by Goel et al of 53% [17].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The recurrence rate of GBC jaundice patients is usually high, as seen in the study by Goel et al of 53% [17].…”
Section: Discussionmentioning
confidence: 92%
“…Another study by Goel et al reported a resectability rate of 62% using neoadjuvant chemotherapy. Moreover, 44% of these patients had benign etiology as the cause of obstructive jaundice [ 17 ]. The resectability rate in our study was around 41.5%, even in advanced cases and without the use of neoadjuvant chemotherapy in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations